Rhodium: Python Library for Many-Objective Robust Decision Making and Exploratory Modeling. Issue 1 (9th June 2020) - Hadjimichael, Antonia; Gold, David; Hadka, David; Reed, Patrick
Rhodium is an open source Python library for robust decision making (RDM), many-objective robust decision making (MORDM), and exploratory modeling. These decision-support frameworks enable the identification of robust strategies for the management of complex environmental systems, by evaluating the tradeoffs among candidate strategies, and characterizing their vulnerabilities. Robust strategies refer to management options that perform sufficiently well or acceptably under a range of potential system conditions, rather than optimally in a single, nominal state of the world. Exploratory modeling allows for the simulation of the system under an ensemble of states of the world, so as to discover the ones with consequential effects on the system [1 ]. Rhodium facilitates rapid application of the RDM and MORDM frameworks by providing a suite of optimization, visualization, scenario discovery, and sensitivity analysis functions. Rhodium is written in Python and can interface with models written in Python, C and C++, Fortran, R, and Excel. The source code is freely available athttps://github.com/Project-Platypus/Rhodium .